2003
DOI: 10.1097/01.hdx.0000050410.54258.24
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic Considerations in Anesthesia

Abstract: This article focuses on new findings leading to improved understanding of the pathophysiology and mechanisms of potential drug interactions between anesthetic drugs or techniques and cardiovascular medications in patients scheduled for surgery. Only the most frequently used drugs are reviewed. Elective surgery provides the luxury to consider these risks and alter therapy accordingly. Under urgent circumstances, however, the increased risks associated with these agents should be anticipated with the goal to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 164 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Many of the antiplatelet drugs are relative newcomers to drug formularies and to date the clinical studies reported are inconclusive about the risk to patients undergoing surgery. This is because of discrepancies arising relating to the heterogeneity of the populations studied, the varied types of surgical procedures and differing dosing strategies [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the antiplatelet drugs are relative newcomers to drug formularies and to date the clinical studies reported are inconclusive about the risk to patients undergoing surgery. This is because of discrepancies arising relating to the heterogeneity of the populations studied, the varied types of surgical procedures and differing dosing strategies [1].…”
mentioning
confidence: 99%
“…For patients undergoing elective surgery, it is certainly wise to delay their procedures until the antiplatelet effects of these medications have subsided. Under urgent circumstances, the increased risks associated with these agents should be anticipated, with the goal of minimising adverse effects while maintaining optimal cardiovascular function perioperatively [1].…”
mentioning
confidence: 99%